The practice of cost-benefit analysis in transport: The case of France - Emile Quinet (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
The practice of cost-benefit analysis (CBA) has a long tradition in France, dating back to Dupuit (1849), but is still a topical subject. This practice is in fact the result of the combination of economic theory and decision processes regarding project choices. Both of these are constantly changing: advances and progress in the theory mean that the technical methods and tools used are constantly improving, while changes to decision processes and institutional organisations are transforming evaluation requirements. In some countries, the process of constant change has been very fast indeed. This is currently true in France, where major transformations are occurring. We are now leaving a period during which the doctrine was based on the strict application of traditional economic calculation and the pre-eminence of a single criterion predicated on surplus theory, and entering a phase very firmly focused on multi-criteria analysis in which traditional CBA is only one of the assessment factors. These transformations are under way, although not finished yet. However, the situation is already sufficiently clear-cut for this paper to outline the main points and pass judgment on their causes and effects.
Keywords: 330